2023
DOI: 10.31616/asj.2022.0155
|View full text |Cite
|
Sign up to set email alerts
|

Spine Fractures of Patients with Ankylosing Spondylitis and Diffuse Idiopathic Skeletal Hyperostosis: Fracture Severity and Injury-Related Mortality at a Level I Trauma Center

Abstract: Retrospective review of prospectively collected cohort.Purpose: To identify differences in treatment and mortality of spine fractures in patients with ankylosing conditions of the spine. Overview of Literature: Ankylosing spondylitis (AS) and diffuse idiopathic skeletal hyperostosis (DISH) are the two most common etiologies of ankylosing spinal disorder (ASD). However, studies on the treatment and outcomes of spine fractures in AS and DISH patients remain few. Methods: Patients presenting with a spine fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Stresses were also greatest in the anterior column, with a progressive decline in the middle and posterior columns. This concords with prior examinations of fracture pattern in DISH, which have shown disproportionate involvement of the anterior and middle columns in DISH fractures [ 41 , 43 , 44 ]. It is noted that most fractures occur between regions of hypertrophic ossification and at junctional regions where autofused segments abut mobile segments, likely due to the generation of stress risers at these points.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Stresses were also greatest in the anterior column, with a progressive decline in the middle and posterior columns. This concords with prior examinations of fracture pattern in DISH, which have shown disproportionate involvement of the anterior and middle columns in DISH fractures [ 41 , 43 , 44 ]. It is noted that most fractures occur between regions of hypertrophic ossification and at junctional regions where autofused segments abut mobile segments, likely due to the generation of stress risers at these points.…”
Section: Discussionsupporting
confidence: 65%
“…Subanalysis demonstrated severely reduced mid-fused segment HUs in AS (74) compared to DISH patients (123), which may help to explain the more severe fractures noted in patients with AS as compared to DISH. A recent study by Chen and colleagues examined 137 patients with AS or DISH presenting with trauma, and they found that AS patients suffered more severe fractures compared to DISH and more frequently underwent surgery for these injuries [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is one of the leading causes of death among young people worldwide. [4][5][6][7] Among trauma patients, 50% of deaths occur within the first hour and 30% within a few hours. [8] High proficiencies are required for rapid treatment to reduce preventable mortality.…”
Section: Introductionmentioning
confidence: 99%